Analisis literasi keuangan dan pendapatan terhadap keputusan berinvestasi - Vansiska, Vansia; Tobing, Vargo Christian L. (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this study was to find out the effect of financial literacy and income variables on investment decisions at several universities in Batam City. The research The population of this study consisted of accounting students in the city of Batam with a total of 1,141 people. Determination of the sample using purposive sampling technique with a total sample of 100 people. The data that has been collected will be tested using the SPSS application to determine the results of the descriptive statistical analysis test, quality test, classical assumption test, multiple linear regression test, t test, F test and test of the coefficient of determination. The results of testing the research hypothesis indicate that financial literacy and income have a positive and significant effect on student investment decisions. The results of the R Square test in this study showed that the magnitude of the influence of the independent variables in this study on the dependent variable was 63.7 percent, the other 36.3 percent were influenced by other independent variables. which was not found in this study.